Successes and obstacles in implementing social health insurance in developing and middle-income countries: A scoping review of 5-year recent literatures - Jamal, Mohammad Husni; Abdul Aziz, Aznida Firzah; Aizuddin, Azimatun Noor; Aljunid, Syed Mohamed (Frontiers in Public Health, 2022)
Background: Social Health Insurance (SHI) as a form of health finance mechanism had been implemented in many countries with the aim of achieving Universal Health Care (UHC) for its population. In attempting to emulate the successes of SHI in many developed countries, many developing and Lower-and-Middle-Income countries (LMICs) are also attempting to follow suit. However, the implementation of SHI was not without problems and obstacles. Objectives: The purpose of this scoping review is to study the various developments of SHI globally in its uses, implementation, successes and obstacles within the last 5 years from 2017 to 2021. Methods: Using 3 databases which are PubMed, EBSCO and Google Scholar, we reviewed all forms of articles on SHI including grey literature. The PRISMA-ScR protocol is adapted as the guideline. We used the following search terms: social health insurance, national health insurance and community health insurance. Results: A total of 57,686 articles were screened and subsequently 46 articles were included in the final review. Results showed that the majority of SHI studies were in China and African countries, both of which were actively pursuing the SHI programs to achieve UHC. China was still regarded as a developing country. There were also recent experiences from other Asian countries but only a few from Europe, USA and South America. Conclusion: The implementation of SHI to achieve UHC was desirable but would need to consider several factors and issues. This was especially so in developing and LMICs. Eventually, full UHC would only be possible with a combination of general taxation and SHI.